A Complete Sample of Ultraluminous X-Ray Source Host Galaxies - Swartz, D.; Soria, Roberto; Tennant, A.; Yukita, M. (Institute of Physics Publishing, Inc., 2011)
One hundred seven ultraluminous X-ray sources (ULXs) with 0.3–10.0 keV luminosities in excess of 1039 erg s−1 are identified in a complete sample of 127 nearby galaxies. The sample includes all galaxies within 14.5Mpc above the completeness limits of both the Uppsala Galaxy Catalogue and the Infrared Astronomical Satellite survey. The galaxy sample spans all Hubble types, a four-decade range in mass, 7.5 < log(M/M_) < 11.4, and in star formation rate, 0.0002 < SFR(M_ yr−1) ≤ 3.6. ULXs are detected in this sample at rates of one per 3.2×1010M_, one per ~0.5M_ yr−1 star formation rate, and one per 57 Mpc3 corresponding to a luminosity density of ~2 × 1037 erg s−1 Mpc−3. At these rates we estimate as many as 19 additional ULXs remain undetected in fainter dwarf galaxies within the survey volume. An estimated 14 objects, or 13%, of the 107 ULX candidates are expected to be background sources. The differential ULX luminosity function shows a power-law slope α ~ −0.8 to −2.0 with an exponential cutoff at ~20 × 1039 erg s−1 with precise values depending on the model and on whether the ULX luminosities are estimated from their observed numbers of counts or, for a subset of candidates, from their spectral shapes. Extrapolating the observed luminosity function predicts at most one very luminous ULX, LX ~ 1041 erg s−1, within a distance as small as 100 Mpc. The luminosity distribution of ULXs within the local universe cannot account for the recent claims of luminosities in excess of 2 × 1041 erg s−1, requiring a new population class to explain these extreme objects.